Implementation of Novel Mode for Evaluation of MYCN Amplification that can Predict Outcome in Patients with Neuroblastoma - Ilieva Gordana; Kocova Mirjana; Conevska Biljana; Shukarova Angelovska, Elena (My University, 2020)
Background: Neuroblastoma tumorigenesis is a cascading process where several cytogenetic findings can be detected MYCN oncogene is a potent transcription factor that controls main cell functions. Several genetic methods can be applied in order to detect quantity of amplified MYCN oncogene. The purpose of this study is to improve the technique of determining the amplification of the MYCN oncogene in each evaluated tumor cell. Results: Standard G banded karyotype and fluorescence in-situ hybridization (FISH) on interphase nuclei using N-MYC amplification probe was performed in five patients with different clinical presentation of neuroblastoma. Both bone marrow and tumor tissue were analysed in four and in one patient only tumor tissue. Follow up study was performed in order to obtain additional prognostic information. Additional grading system was implemented to obtain MYCN amplification status. Significant amount of amplified units was detected in two patients with adverse outcome, which was not the case in other three patients who had minor or none amplification of MYCN. Furthermore, there were no cells with significant MYCN amplification in more than 30% of the cell surface in patient three and four that represented a good prognostic factor for their survival. Conclusion: Our study confirmed that patients with both chromosomal changes and significant MYCN amplification are characterized with aggressive clinical course. Accuracy in quantifying the amount of MYCN amplification is crucial in planning the therapeutic approach. FISH is proved to be rapid, sensitive, and reliable method for detection of MYCN oncogene amplification in routinely processed samples
Keywords: Neuroblastoma; MYCN amplification; Cytogenetics; fluorescent in-situ hybridization